God's propositional omniscience: a defence of the strictly restricted account - Zarepour, Mohammad Saleh ca. 20./21. Jh. (Religious studies, 2020)
By discussing three different understandings of the notion of God's propositional omniscience from a theistic point of view, I show that the strictly restricted account (SPO) - according to which God knows all true propositions that He can know - is preferable to the two other candidates as the standard interpretation of God's propositional omniscience. To establish this conclusion, I argue that Pruss's argument that strictly restricted omniscience (SPO) entails full omniscience (FPO) fails because it relies on a flawed construal of the former thesis. I propose an alternative construal for strictly restricted omniscience and defend it against some potential objections.